2017
DOI: 10.1136/bjsports-2017-097865
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal injury profiles in professional Women’s Tennis Association players

Abstract: This study prospectively analysed injury profiles, including severity across an entire season of professional tennis, and investigated the relationship between training/match loads and injury. These data may help medical professionals develop injury risk identification and prevention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
1
23
0
1
Order By: Relevance
“…This is in contrast to previous studies that reported very few fractures in recreational and professional players. 5,10,19 A higher fracture incidence was already recognized by Gaw et al, 9 at 14.6% in US emergency room visits. Because that study and ours investigated patients seeking care in the emergency department, it seems difficult to compare the cohorts with other previous reports on injury rates during tournaments and the ATP tour.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is in contrast to previous studies that reported very few fractures in recreational and professional players. 5,10,19 A higher fracture incidence was already recognized by Gaw et al, 9 at 14.6% in US emergency room visits. Because that study and ours investigated patients seeking care in the emergency department, it seems difficult to compare the cohorts with other previous reports on injury rates during tournaments and the ATP tour.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have investigated injury data in professional, elite, collegiate, and junior players. 5,8,10,23 25,33 Data from a 5-year summary from the ATP tour showed that the spine was the region with the highest injury rate among players, followed by lower similar rates for foot/ankle, thigh, and shoulder injuries. 8 In contrast, data from several other studies have shown that most tennis injuries occur in the lower extremity (31%-67%), followed by the upper extremity (20%-49%) and finally the trunk (3%-21%).…”
mentioning
confidence: 99%
“…Both individual16 and team17–19 performance can be explained, at least in part by training load, with higher training loads generally associated with better performance. Equally, a large body of evidence has emerged suggesting that inappropriately prescribed training load may increase injury risk20–25 and pain 26. Based on these findings, a myopic view would be that ‘load’ explains all injuries.…”
Section: Myth 1: Load Explains All Injuriesmentioning
confidence: 99%
“…The serve is the most demanding stroke in tennis, with supra-physiologic forces through the shoulder and elbow [6,13]. Thus, a considerable proportion of injuries in tennis players are located in the dominant shoulder, with an incidence of 8.2 injuries per 1000 playing hours in tennis matches, accounting for 15.9% of all overuse injuries in elite junior tennis players [6,14,15]. These injuries are mainly caused by the conjunction of unilateral and repetitive tennis strokes and biomechanical and training load errors, which lead to alterations in the shoulder ROM [16,17], and to imbalances in the muscle strength [18,19].…”
Section: Introductionmentioning
confidence: 99%